Multifunctional rapid shape memory composite frozen gel as well as preparation method and application thereof
By preparing a cryogel composed of animal small intestinal submucosa and polyurethane polymer composite, the problem of limited hemostatic effect of existing hemostatic materials was solved, achieving a multifunctional effect of rapid hemostasis and tissue repair.
Patent Information
- Application Number
- CN202510411931.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-12-26
AI Technical Summary
Existing sponge-based hemostatic products have limited hemostatic effects and cannot simultaneously achieve rapid emergency hemostasis and in-situ tissue repair after hemostasis.
A multifunctional, rapid shape memory composite cryogel was prepared by combining animal small intestinal submucosa with polyurethane polymers, followed by low-temperature crosslinking and freeze-drying. The material exhibits self-wetting, self-expansion, self-reinforcing, and self-degrading properties.
It achieves rapid absorption of fluid, promotes blood clotting, forms stable blood clots, and is degradable after hemostasis, promoting tissue repair. It is suitable for surgery and trauma emergency care.
Smart Images

Figure CN121197487A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medical material preparation technology, specifically relating to a multifunctional rapid shape memory composite cryogel, its preparation method, and its uses. Background Technology
[0002] Uncompressible bleeding frequently occurs in daily life and military training. Although the body's clotting function is activated, it is still difficult to control the bleeding in the absence of effective hemostatic measures. This can lead to massive blood loss, hypotension, multiple organ failure, and infection of the bleeding wound, often resulting in a very high mortality rate. Sponge-based hemostatic products have the characteristics of high blood absorption and rapid expansion, which can effectively seal the bleeding point and have become a common strategy for controlling deep uncompressible massive bleeding. However, the hemostatic effect of commonly used sponge-based hemostatic products on the market is limited, and they cannot simultaneously provide rapid emergency hemostasis and guide in-situ tissue repair after hemostasis.
[0003] Therefore, developing a hemostatic material that also promotes in-situ tissue repair after hemostasis, while ensuring hemostatic performance, is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0004] In order to solve the above-mentioned problems in the prior art, the purpose of this invention is to provide a multifunctional rapid shape memory composite cryogel, its preparation method and uses.
[0005] To achieve the above objectives, the present invention adopts the following technical solution:
[0006] This invention provides a composite cryogel, the raw materials of which include animal small intestinal submucosa digestive fluid and polyurethane polymer; the animal small intestinal submucosa digestive fluid is obtained by sequentially treating the animal small intestinal submucosa with decellularization, powdering, and enzymatic digestion, and the mass ratio of the animal small intestinal submucosa to the polyurethane polymer is (0.01-20):1.
[0007] Furthermore, the polyurethane polymer is polyurethane or disulfide-modified polyurethane; the mass ratio of the animal small intestinal submucosa to the polyurethane polymer is (0.1-11):1.
[0008] Furthermore, the mass ratio of the animal's small intestinal submucosa to the polyurethane polymer is 7:1, and the animal is a pig.
[0009] Furthermore, the disulfide-modified polyurethane is obtained by reacting polycaprolactone diol 2000, 2,2'-dithiodiethanol, isophorone diisocyanate and 2,2-dimethylolbutyric acid as raw materials; the molar ratio of polycaprolactone diol 2000, 2,2'-dithiodiethanol, isophorone diisocyanate and 2,2-dimethylolbutyric acid is 1:(0.1~5):(0.1~10):(0.1~5).
[0010] Furthermore, the molar ratio of polycaprolactone diol 2000, 2,2'-dithiodiethanol, isophorone diisocyanate and 2,2-dimethylolbutyric acid is 1:1:3.45:1.
[0011] Furthermore, the raw materials of the composite cryogel also include tannic acid, and the final concentration of the tannic acid is 0.1-5 mg / mL.
[0012] Furthermore, the final concentration of the tannic acid is 0.5 mg / mL.
[0013] The present invention also provides a method for preparing the above-mentioned composite cryogel, wherein the preparation method comprises mixing animal small intestinal submucosa digestive fluid with polyurethane polymer evenly, adding catalyst, crosslinking at low temperature, pre-freezing crystallization, freeze drying, and sterilization to obtain composite cryogel.
[0014] Furthermore, the preparation method involves uniformly mixing animal small intestinal submucosa digestive fluid, polyurethane polymer emulsion, and tannic acid, adding a catalyst, crosslinking at low temperature, pre-freezing crystallization, freeze-drying, and sterilization to obtain a composite cryogel.
[0015] Furthermore, the mass fraction of the polyurethane polymer emulsion is 20%.
[0016] Further, the catalyst is 1-ethyl-(3-dimethylaminopropyl)carbodiimide; the low-temperature crosslinking temperature is -10 to 10°C; the low-temperature crosslinking time is 6 to 48 hours; the pre-freezing crystallization temperature is -40 to 0°C; the pre-freezing crystallization time is 12 to 48 hours; and the sterilization is ethylene oxide sterilization.
[0017] Furthermore, the low-temperature crosslinking temperature is 4°C; the low-temperature crosslinking time is 24 hours; the pre-freezing crystallization temperature is -20°C; and the pre-freezing crystallization time is 24 hours.
[0018] The present invention also provides the use of the above-mentioned composite cryogel in surgery and trauma emergency care.
[0019] The present invention has achieved the following beneficial effects:
[0020] This invention utilizes a composite crosslinking and chemical modification of porcine small intestinal submucosa (SIS) and polyurethane to prepare a rapid shape memory composite cryogel with the following advantages: 1) "Self-wetting": The material has excellent hydrophilicity, eliminating the need for pre-use moistening with saline solution. Even in a dry state, it can rapidly absorb liquids up to 40 times its own weight (completely absorbing surface droplets within 40ms); 2) "Self-expansion": The cryogel possesses outstanding shape memory capabilities, rapidly recovering its volume within 1.8s, creating compressive stress on deep tissues and effectively sealing bleeding sites; 3) "Self-reinforcing": The material exhibits procoagulant activity, significantly promoting platelet adhesion and activation, accelerating the body's coagulation process, and enhancing the mechanical properties of the sponge by forming a stable blood clot structure; 4) "Self-degradation": After hemostasis, the cryogel does not require secondary removal, degrading in vivo and promoting in-situ tissue repair. This invention has broad application prospects in surgery, trauma emergency care, and other fields.
[0021] Obviously, based on the above description of the present invention, and according to common technical knowledge and conventional methods in the field, various other modifications, substitutions or alterations can be made without departing from the basic technical concept of the present invention.
[0022] The following detailed embodiments further illustrate the above-described content of the present invention. However, this should not be construed as limiting the scope of the present invention to the following examples. All technologies implemented based on the above-described content of the present invention fall within the scope of the present invention. Attached Figure Description
[0023] Figure 1 (a) Statistical graph of liquid absorption capacity of PU-SIS cryogels with different crosslinking ratios; (b) Shape memory time of PU-SIS cryogels with different crosslinking ratios; (c) Stress-strain curves of PU-SIS cryogels with different crosslinking ratios after absorbing PBS; and (d) Surface morphology changes.
[0024] Figure 2 Infrared spectra of (a) PU, PUS and (b) SIS, PU-SIS, PUS-SIS and PUS-SIS@TA.
[0025] Figure 3 (a) Absorption of PBS by each group of cryogels; (b) Liquid-triggered shape memory photographs of each group of cryogels; Absorption rates of each group of cryogels to (c) PBS and (d) anticoagulated whole blood; Shape memory recovery time of each group of cryogels after absorption of (e) PBS and (f) anticoagulated whole blood (*p<0.05, ****p<0.0001, ns: no significant difference).
[0026] Figure 4(a) CCK-8 results and (b) live / dead staining results of BRL cells at 24h, 48h and 72h after cryogel treatment (scale bar = 200μm) (ns: no significant difference).
[0027] Figure 5 (a) Scanning electron microscopy images showing the adhesion of erythrocytes and platelets on commercial gelatin sponges and cryogels of different components; (b) Immunofluorescence staining of CD42b and CD62p showing the adhesion and activation of platelets on different materials.
[0028] Figure 6 Photographs showing the hemostatic effects of (a) the blank control group, the commercial gelatin sponge group, and the cryogel groups with different components in a rabbit lethal liver perforation model; (b) HE staining results of the liver perforation site after hemostasis with PUS-SIS@TA cryogel; (c)-(d) total blood loss and hemostasis time of the blank control group, the commercial gelatin sponge group, and the cryogel groups with different components (**p<0.01,***p<0.001,****p<0.0001).
[0029] Figure 7 (a) Representative photographs of wound healing at the site of lethal liver perforation in rabbits at 1, 3, and 5 weeks in different groups; (b) HE staining of regenerated tissue at the liver perforation site in different groups at 5 weeks; (c) Blood biochemical parameters used to evaluate the degree of liver injury in different groups at 3 days and 1 week (*p<0.05, **p<0.01, ***p<0.001,
[0030] ****p<0.0001).
[0031] Figure 8 The subcutaneous morphology of PU-SIS, PUS-SIS, and PUS-SIS@TA cryogels after 1, 2, 3, and 4 weeks of subcutaneous implantation in rats. Detailed Implementation
[0032] The raw materials and equipment used in this invention are all known products, obtained by purchasing commercially available products.
[0033] The following experiments, for which no temperature is specified, are reactions conducted under normal temperature conditions, which is room temperature, or 25–30°C.
[0034] (1) Preparation of digestive fluid from the submucosa (SIS) of the small intestine of pigs
[0035] Fresh porcine small intestinal submucosa tissue was decellularized, and the decellularized SIS was ground into powder using a ball mill and passed through a 200-mesh sieve to obtain SIS powder. 0.3 g of SIS powder was added to 30 mL of hydrochloric acid solution (pH = 2), followed by 30-70 mg of pepsin. The mixture was stirred at 25°C for 24-96 h to digest, yielding a 1% SIS digestion solution.
[0036] (2) Preparation of polyurethane (PU) emulsion
[0037] 1. Add polycaprolactone diol 2000 (PCL2000) and isophorone diisocyanate (IPDI) in a molar ratio of 2:3.45 into a three-necked flask. Set up a support to fix the mixture on the support. Heat the oil bath to 74°C and stir thoroughly for 1 hour. Then, add a catalytic amount of stannous octoate (2-3 drops of stannous octoate per 50g of reaction system) and allow it to react fully for 3-4 hours to obtain the prepolymer.
[0038] 2. Cool the prepolymer from 74℃ to 54℃. Dissolve 2,2-dimethylolbutyric acid (DMBA) thoroughly in acetone solution (enough to completely dissolve the polymer), then slowly add it to the prepolymer and continue stirring for 3-4 hours. (The molar ratio of DMBA to IPDI is 1:3.45)
[0039] 3. Add 4.5 mL of triethylamine (TEA) to the reaction system and stir at room temperature for 30 min to neutralize. (TEA:DMBA molar ratio is 1:1)
[0040] 4. The above reaction product was slowly added dropwise to a beaker containing 200 mL of pure water, 6 mL of triethylamine, and 50 mL of acetone, and stirred at high speed for emulsification (1300 rpm, 2 h) to obtain crude PU emulsion product.
[0041] 5. The crude PU emulsion was thoroughly rotary evaporated at 50-60℃. A dialysis bag with a molecular weight cutoff of 3500 was used to dialyze the evaporated crude PU emulsion. The mixture was then placed on a magnetic stirrer for 3 days to obtain a purified PU emulsion. The water was changed every 6 hours. The purified PU emulsion was then rotary evaporated at 60-80℃ to obtain a PU emulsion with a mass fraction of 20%.
[0042] (3) Preparation of disulfide bond modified polyurethane (PUS) emulsion
[0043] 1. Polycaprolactone diol 2000 (PCL2000), 2,2'-dithiodiethanol and isophorone diisocyanate (IPDI) were added to a three-necked flask in a molar ratio of 1:1:3.45. The mixture was fixed on a support frame, heated to 74°C in an oil bath, and stirred thoroughly for 1 hour. Then, a catalytic amount of stannous octoate was added dropwise (2-3 drops of stannous octoate per 50g of reaction system) and allowed to react fully for 3-4 hours to obtain prepolymer 2.
[0044] 2. Cool prepolymer 2 from 74℃ to 54℃, then slowly pour the fully dissolved 2,2-dimethylolbutyric acid (DMBA) into a certain amount of acetone solution and continue stirring for 3-4 hours. (The molar ratio of DMBA to IPDI is 1:3.45)
[0045] 3. Add 4.5 mL of triethylamine (TEA) to the reaction system and stir at room temperature for 30 min to neutralize. (TEA:DMBA molar ratio is 1:1)
[0046] 4. The above reaction product was slowly added dropwise to a beaker containing 200 mL of pure water, 6 mL of triethylamine, and 50 mL of acetone, and stirred at high speed for emulsification (1300 rpm, 2 h) to obtain crude PUS emulsion product.
[0047] 5. The crude PUS emulsion was thoroughly rotary evaporated at 50-60℃. The crude PUS emulsion was then dialyzed using a dialysis bag with a molecular weight cutoff of 3500. The emulsion was then placed on a magnetic stirrer for 3 days to obtain a purified PUS emulsion. The water was changed every 6 hours. The purified PUS emulsion was then rotary evaporated at 60-80℃ to obtain a 20% PUS emulsion.
[0048] Example 1: Preparation of PU-SIS cryogel
[0049] 1. Add 1% SIS digestion solution and 20% PU emulsion (control the mass ratio of SIS to 20% PU emulsion in the raw materials to be 7:5, that is, control the mass ratio of SIS to PU in the raw materials to be 7:1) to a beaker, and stir at 300 rpm for 10 minutes to mix thoroughly (in an ice water bath).
[0050] 2. Add a certain amount of catalyst 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) solution (the final concentration of EDC in the whole system is 5 mg / mL) to the well mixed system in step 1, adjust the speed to 500 rpm and stir for 3 min, then pour it into the mold, and then place it in a refrigerator at 4℃ for low-temperature crosslinking for 24 h.
[0051] 3. After cross-linking is completed, place the mold together in a -20℃ freezer for pre-freezing and crystallization for 24 hours, and then freeze dry it in a freeze dryer.
[0052] 4. After immersing and washing the freeze-dried material repeatedly in deionized water, pre-freeze it in a -20℃ freezer and then freeze-dry it again.
[0053] 5. The freeze-dried material is sterilized with ethylene oxide to obtain PU-SIS cryogel.
[0054] Example 2: Preparation of PUS-SIS cryogel
[0055] The preparation method of Example 1 was used, except that 20% PU emulsion was replaced with 20% PUS emulsion to prepare PUS-SIS cryogel.
[0056] Example 3: Preparation of PUS-SIS@TA cryogel
[0057] The preparation method of Example 1 was followed, except that 20% PU emulsion was replaced with 20% PUS emulsion and tannic acid (TA) with a final concentration of 0.5 mg / mL to prepare PUS-SIS@TA cryogel.
[0058] Comparative Example 1: Preparation of porcine small intestinal submucosa (SIS) cryogel
[0059] A 1% SIS digestive solution was prepared by referring to the method described in (1) above for the preparation of SIS digestive solution in the submucosa of the small intestine. The SIS digestive solution was then freeze-dried to form a SIS cryogel.
[0060] The following experimental examples demonstrate the beneficial effects of the present invention.
[0061] Experimental Example 1: Screening of Crosslinking Ratio of PU-SIS Cryogel
[0062] Taking PU-SIS cryogel as an example, the ratio of SIS and polyurethane polymers in cryogel was explored.
[0063] The preparation method of Example 1 was used as a reference, except that the mass ratio of SIS to PU was controlled to be 0.1-11:1. The crosslinking ratio of PU-SIS cryogel was explored and screened within the range of 0.1-11:1 mass ratio of SIS to PU.
[0064] like Figure 1As shown in Figure a, the liquid absorption capacity of PU-SIS cryogels continuously increases with the increase of SIS content. Cryogels with a crosslinking ratio of PU-SIS7 (i.e., a SIS to PU mass ratio of 7:1) exhibit the strongest liquid absorption capacity, capable of absorbing up to approximately 40 times their own weight in PBS. However, with further increases in SIS content, the liquid absorption capacity of PU-SIS continuously decreases, such as... Figure 1 As shown in cd, the maximum compressive stress of PU-SIS9 after absorbing PBS to saturation is significantly lower than that of PU-SIS5 and PU-SIS7. Furthermore, the surface structure of PU-SIS9 collapses after absorbing PBS droplets, indicating that further increases in SIS content reduce the stable mechanical structure inside the cryogel, leading to decreased mechanical properties. The intact structure of the cryogel is disrupted after PBS absorption, causing PBS to leak out, resulting in decreased absorbency. Figure 1 Figure b shows that the shape memory capability of PU-SIS9 is also reduced compared to PU-SIS5 and PU-SIS7.
[0065] In summary, the cryogel with the PU-SIS7 crosslinking ratio exhibits the strongest liquid absorption capacity and maintains a stable internal structure to the greatest extent after absorbing PBS, effectively locking in the internal liquid and preventing its loss. Therefore, PU-SIS7, i.e., a cryogel with a crosslinking ratio of 7:1 between SIS and polyurethane polymers, was selected as the preferred crosslinking ratio.
[0066] The samples used in the following experimental examples were all cryogels with a crosslinking ratio of 7:1.
[0067] Experimental Example 2: Characterization of cryogels
[0068] Unless otherwise specified, SIS refers to a cryogel formed by direct freeze-drying of SIS digestion solution; PU-SIS refers to a cryogel formed by cross-linking PU emulsion and SIS digestion solution; PUS-SIS refers to a cryogel formed by cross-linking PUS emulsion and SIS digestion solution; and PUS-SIS@TA refers to a cryogel formed by cross-linking PUS emulsion and SIS digestion solution and further modified with TA. The concentrations and ratios of PU emulsion, PUS emulsion, and SIS gel remain consistent in the different component cryogels.
[0069] The chemical structures of SIS, PU, PUS, PU-SIS, PUS-SIS, and PUS-SIS@TA prepared according to the above method were characterized by Fourier transform infrared absorption spectroscopy. Figure 2As shown in the infrared spectra of PU and PUS in a, the characteristic absorption peak of isocyanate group (-NCO) near 2245 cm⁻¹ disappeared, indicating that the IPDI reaction was complete. A stretching vibration peak of carbonyl group (C=O) appeared at 1731 cm⁻¹, which is one of the important characteristic peaks of urethane group (-NH-CO-O-). Since urethane group is the main structural unit of polyurethane, the appearance of this peak confirms the existence of urethane structure. At the same time, the bending vibration peak of imino group (-NH-) appeared at 1536 cm⁻¹, further confirming the successful preparation of polyurethane.
[0070] Compared to PU, PUS exhibits a new characteristic absorption peak for disulfide bonds (-SS-) at 500-539 cm⁻¹, confirming the presence of disulfide bond structures in PUS. PU-SIS is obtained by cross-linking polyurethane and porcine small intestinal submucosa through the reaction of amino and carboxyl groups to form amide bonds. Figure 2 As shown in b, the characteristic peaks of urethane groups in PU can still be seen within the corresponding wavenumber range. Compared to the infrared spectrum of PU, the PU-SIS spectrum shows peaks in the 1680-1630 cm⁻¹ range. -1 A new absorption peak appeared at the position, attributed to the C=O stretching vibration peak of the amide bond, which is different from the C=O stretching vibration peak of the urethane group in PU. Furthermore, in the 1530-1580 cm⁻¹... -1 The presence of NH bending vibration peaks of amide bonds further confirms the formation of amide bonds.
[0071] Like PU-SIS, PUS-SIS and PUS-SIS@TA groups also exhibited characteristic peaks of amide bonds, proving that all three groups of materials were successfully crosslinked.
[0072] Experiment Example 3: Hydrophilicity and Shape Memory of Cryogels
[0073] Hydrophilic cryogels can quickly absorb water from the blood, making it easier for blood cell components (such as red blood cells and platelets) to adhere to and accumulate in the pore structure of the sponge, thus helping to stop bleeding quickly.
[0074] The hydrophilicity and shape memory of the cryogels prepared in Examples 1-3 were tested, and the results are as follows: Figure 3 As shown in Figure a, each group of cryogels exhibits superior absorption capacity for PBS; PUS-SIS@TA can completely absorb the PBS on its surface within 40 ms. The PU-SIS, PUS-SIS, and PUS-SIS@TA groups all demonstrate extremely strong liquid absorption capabilities, such as... Figure 3 As shown in CD, it can absorb 40 times its own weight in PBS and anticoagulated whole blood.
[0075] Similarly, shape memory is also crucial for hemostatic cryogels, from Figure 3As can be seen in b, each group of cryogels can be compressed into a flat shape when not in use, which facilitates storage and portability. The PU-SIS, PUS-SIS, and PUS-SIS@TA groups all exhibit good shape memory capabilities, such as... Figure 3 As shown in ef, both PBS and anticoagulated whole blood can achieve rapid shape memory within 1.8 seconds. However, the SIS group turns into a gel state under the influence of PBS and anticoagulated whole blood, exhibiting no shape memory ability.
[0076] Experimental Example 4: Cell Compatibility of Cryogels
[0077] In a 24-well plate, inoculate 5 × 10⁶ cells per well. 4 BRL cells were cultured overnight until they adhered to the culture vessel. The initial culture medium was then discarded and replaced with the extraction medium of PU-SIS, PUS-SIS, and PUS-SIS@TA cryogels. The cells were then cultured in an incubator, with fresh extraction medium / culture medium replaced every 24 hours.
[0078] Preparation of extracts: Sterilized PU-SIS, PUS-SIS, and PUS-SIS@TA cryogels were immersed in DMEM complete medium at a ratio of 0.2 g / mL and treated in an incubator at 37°C for 72 hours. The treated extracts were collected, centrifuged at 1000 rpm for 10 min, and the supernatant was collected and stored at 4°C.
[0079] Live / dead staining: Dilute the calcein stock solution and propidium iodide stock solution with PBS buffer to prepare a 1 μM live / dead staining working solution. At 24 h, 48 h, and 72 h after continued incubation, remove the extract / medium, wash three times with PBS for 5 min each time. Then add 200 μL of the live / dead staining working solution to each well and incubate at room temperature in the dark for 30 min.
[0080] Observation and recording: Remove the live and dead staining solution, wash three times with PBS for 5 minutes each time, and observe the cells in the well plate using a two-photon confocal microscope. Observe the live cells with yellow-green fluorescence at an excitation wavelength of 490 nm and observe the dead cells with red fluorescence at an excitation wavelength of 545 nm. Record and save the images.
[0081] Good cell compatibility is one of the basic requirements for biomaterials. Figure 4 The results showed that the extracts of PU-SIS, PUS-SIS, and PUS-SIS@TA, after co-culturing with rat hepatocyte cell lines (BRL cells) for 24 h, 48 h, and 72 h, did not exhibit cytotoxicity compared to the control group (equal volume of physiological saline), indicating that the materials did not affect cell proliferation. This was further supported by live / dead staining results (…). Figure 4(b) It can be seen that the field of view is almost entirely composed of live cells with green fluorescence, with very few dead cells showing red fluorescence. Furthermore, after co-culturing with the cryogel extract, the cells maintained their elongated spindle shape and were in good condition. In conclusion, the cryogel did not affect cell proliferation and activity, indicating good cell compatibility.
[0082] Experimental Example 5: Hemostatic Mechanism of Cryogel
[0083] (1) Red blood cell adhesion test
[0084] a) Take a certain amount of fresh rabbit anticoagulated whole blood into a centrifuge tube, and then centrifuge it (200g, 15min) to separate the plasma, white blood cell layer and red blood cell precipitate.
[0085] b) Carefully aspirate the lower layer of red blood cell precipitate, and then resuspend it in an equal volume of physiological saline to form a red blood cell suspension.
[0086] c) Commercial gelatin sponges, PU-SIS, PUS-SIS and PUS-SIS@TA cryogels were all cut into 10mm×10mm×2mm cubes, and then 200μL of red blood cell suspension was added to each group of samples and incubated at 37℃ for 20min.
[0087] d) Then carefully wash the sample 5 times with PBS buffer to remove any red blood cells that are not adhering to the sample surface.
[0088] e) The sample was then immersed in 4% paraformaldehyde and placed in a 4°C refrigerator for 2 hours to fix the cell morphology.
[0089] f) The samples were then sequentially immersed in ethanol solutions of gradually increasing concentrations (50%, 60%, 70%, 80%, 90%, 100%), and each concentration was dehydrated for 15 min.
[0090] g) The sample was dried with CO2 and sputtered with gold, and then the adhesion was observed and recorded using a scanning electron microscope.
[0091] (2) Platelet adhesion test
[0092] Platelets were extracted from fresh rabbit anticoagulated whole blood using a rabbit peripheral blood platelet separation kit. Platelet adhesion in each group of samples was then evaluated. The specific experimental steps are as follows:
[0093] a) Take 8 mL of fresh rabbit anticoagulated whole blood and dilute it with an equal volume of diluent.
[0094] b) Add 12 mL of separation solution to the centrifuge tube, then add 6 mL of 60% separation solution to form a separation interface, and then add 16 mL of diluted rabbit anticoagulated whole blood. Centrifuge at room temperature (300 g, 20 min).
[0095] c) After centrifugation, obvious stratification appears in the centrifuge tube. Carefully aspirate the platelet and plasma layers into a new centrifuge tube, add 10 mL of cell washing buffer, and centrifuge again (500 g, 20 min).
[0096] d) Discard the supernatant and resuspend the platelet suspension in 3 mL of physiological saline.
[0097] e) Commercial gelatin sponges, PU-SIS, PUS-SIS and PUS-SIS@TA cryogels were all cut into 10mm×10mm×2mm cubes, and then 200μL of platelet suspension was added to each group of samples and incubated at 37℃ for 20min.
[0098] f) Subsequent operations are the same as the experimental steps in dg in (1) erythrocyte adhesion experiment.
[0099] The hemostatic mechanism of cryogels was investigated using a blood cell adhesion assay. In addition to the PU-SIS, PUS-SIS, and PUS-SIS@TA groups, clinical gelatin sponge was used as a positive control group. Figure 5 Scanning electron microscopy images in Figure a show that, compared to the commercial gelatin sponge group, each cryogel group was able to adhere to and aggregate more blood cells and platelets, while the PUS-SIS@TA group was able to further generate more fibrin network structures, accelerating the hemostasis process. Figure 5 Immunofluorescence staining of CD42b and CD62p in the b group showed platelet activation on different components of the cryogel. The results showed that the PUS-SIS@TA group could adhere to more platelets and accelerate the coagulation process by activating more platelets.
[0100] Experiment Example 6: Hemostatic Effect of Cryogel
[0101] The hemostatic effect of cryogel was evaluated using a rabbit lethal liver perforation hemorrhage model. A 10 mm diameter perforation was created in the rabbit liver using a skin biopsy device, and cryogel was immediately inserted into the perforation site. The bleeding process was recorded until complete hemostasis was achieved. Except for the PU-SIS, PUS-SIS, and PUS-SIS@TA groups, a clinical gelatin sponge was used as the positive control group (i.e., the gelatin group), and no hemostatic treatment was performed as the blank control group. Figure 6 Images of the hemostasis process and the amount of bleeding on the filter paper after hemostasis are shown. The blank control group had the largest area of blood on the filter paper, while the other groups showed obvious hemostasis effects, with the PUS-SIS@TA group having the smallest amount of bleeding. Figure 6 b shows the HE staining results of the liver perforation sealing after hemostasis with PUS-SIS@TA cryogel, demonstrating that the cryogel can closely adhere to the wound surface for effective sealing of the bleeding point. Furthermore, from... Figure 6 Quantitative statistical results of blood loss and hemostasis time in the control group also showed that the average blood loss was 4.32g in the blank control group, while the blood loss in the gelatin, PU-SIS, PUS-SIS, and PUS-SIS@TA groups was 59.3%, 41.2%, 39.4%, and 19.2% of that in the control group, respectively, all significantly less than that in the control group. The PUS-SIS@TA group had the least blood loss (0.83g) and the shortest hemostasis time (44.5s), exhibiting the best hemostatic effect, superior to commercially available light-sensitive adhesive sponges.
[0102] Experimental Example 7: The ability of cryogels to guide in-situ tissue regeneration after hemostasis
[0103] Removing the hemostatic material after hemostasis often causes secondary injury, infection risk, and significant pain for the patient. If the hemostatic material does not need to be removed after hemostasis and is used to guide tissue regeneration in situ, it will benefit the patient's recovery.
[0104] This experiment evaluated the ability of cryogel to guide in situ tissue regeneration after hemostasis by constructing a lethal rabbit liver perforation model. In addition to the PU-SIS, PUS-SIS, and PUS-SIS@TA groups, clinical gelatin sponge was used as a positive control, and electrocoagulation (NC) treatment was used as a negative control. Figure 7 a general sketch and Figure 7 HE staining results of the repair area showed that, except for the NC group, the other four groups could achieve tissue regeneration at the liver perforation site at 5 weeks, with the PUS-SIS@TA group being the closest to normal liver tissue at 5 weeks. Figure 7 Blood biochemistry results for group c showed that, compared to the NC group, the degree of liver damage in the other four groups was significantly reduced at 3 days and 1 week.
[0105] Experimental Example 8: Degradability of Cryogels
[0106] PU-SIS, PUS-SIS, and PUS-SIS@TA cryogels were implanted subcutaneously into rats to assess their tissue compatibility. Rats were euthanized at weeks 1, 2, 3, and 4 post-implantation, and tissue samples were collected and observed at the implantation site. Results are as follows: Figure 8The results showed that no redness or suppuration was observed around the implantation sites of the cryogels in each group, indicating good tissue compatibility. However, at week 4, significant undegraded PU-SIS material was still observed under the skin of rats; while the PUS-SIS and PUS-SIS@TA materials, which were modified with disulfide bonds, showed no obvious material residue at the implantation sites at week 4 after subcutaneous implantation in rats, indicating that the materials had degraded.
[0107] In summary, this invention prepares a rapid shape memory composite cryogel by cross-linking and chemically modifying porcine small intestinal submucosa (SIS) and polyurethane. This cryogel has the following advantages: 1) "Self-wetting": The material has excellent hydrophilicity, eliminating the need for pre-use moistening with saline solution. It can rapidly absorb liquids up to 40 times its own weight in a dry state (complete absorption of surface droplets within 40ms); 2) "Self-expansion": The cryogel possesses outstanding shape memory capabilities, rapidly recovering its volume within 1.8s, creating compressive stress on deep tissues and effectively sealing bleeding sites; 3) "Self-reinforcing": The material exhibits procoagulant activity, significantly promoting platelet adhesion and activation, accelerating the body's coagulation process, and enhancing the mechanical properties of the sponge by forming a stable blood clot structure; 4) "Self-degradation": After hemostasis, the cryogel does not require secondary removal, degrades in vivo, and promotes in-situ tissue repair after hemostasis.
Claims
1. A composite cryogel, characterized in that: The raw materials of the composite cryogel include animal small intestinal submucosa digestive fluid and polyurethane polymers; the animal small intestinal submucosa digestive fluid is obtained by sequentially decellularizing, pulverizing and enzymatically digesting the animal small intestinal submucosa, and the mass ratio of the animal small intestinal submucosa to the polyurethane polymer is (0.01-20):
1.
2. The composite cryogel according to claim 1, characterized in that: The polyurethane polymer is polyurethane or disulfide-modified polyurethane; the mass ratio of the animal small intestinal submucosa to the polyurethane polymer is (0.1-11):1; preferably, the animal is a pig.
3. The composite cryogel according to claim 2, characterized in that: The disulfide-modified polyurethane is obtained by reacting polycaprolactone diol 2000, 2,2'-dithiodiethanol, isophorone diisocyanate and 2,2-dimethylolbutyric acid as raw materials; the molar ratio of polycaprolactone diol 2000, 2,2'-dithiodiethanol, isophorone diisocyanate and 2,2-dimethylolbutyric acid is 1:(0.1~5):(0.1~10):(0.1~5).
4. The composite cryogel according to claim 3, characterized in that: The molar ratio of polycaprolactone diol 2000, 2,2'-dithiodiethanol, isophorone diisocyanate and 2,2-dihydroxymethylbutyric acid is 1:1:3.45:
1.
5. The composite cryogel according to claim 1, characterized in that: The raw materials of the composite cryogel also include tannic acid, and the final concentration of the tannic acid is 0.1-5 mg / mL; preferably, the final concentration of the tannic acid is 0.5 mg / mL.
6. A method for preparing the composite cryogel according to any one of claims 1-5, characterized in that: The preparation method involves mixing animal small intestinal submucosa digestive fluid with a polyurethane polymer, adding a catalyst, crosslinking at low temperature, pre-freezing crystallization, freeze-drying, and sterilization to obtain a composite cryogel.
7. The preparation method according to claim 6, characterized in that: The preparation method involves uniformly mixing animal small intestinal submucosa digestive fluid, polyurethane polymer emulsion, and tannic acid, adding a catalyst, crosslinking at low temperature, pre-freezing crystallization, freeze-drying, and sterilization to obtain a composite cryogel.
8. The preparation method according to claim 6 or 7, characterized in that: The catalyst is 1-ethyl-(3-dimethylaminopropyl)carbodiimide; the low-temperature crosslinking temperature is -10 to 10°C; the low-temperature crosslinking time is 6 to 48 hours; the pre-freezing crystallization temperature is -40 to 0°C; the pre-freezing crystallization time is 12 to 48 hours; and the sterilization is performed using ethylene oxide.
9. The preparation method according to claim 8, characterized in that: The low-temperature crosslinking temperature is 4℃; the low-temperature crosslinking time is 24h; the pre-freezing crystallization temperature is -20℃; and the pre-freezing crystallization time is 24h.
10. Use of the composite cryogel according to any one of claims 1-5 in surgery and trauma emergency care.
Citation Information
Patent Citations
Polyurethane (PU) / small intestine submucosa (SIS) membrane composite material and application thereof
CN104312140A
Gel biological material having shape memory function and preparation method of gel biological material
CN105126171A
Application of SIS cold-set gel in preparation of hemostatic materials
CN108714241A
Polyurethane / small intestinal submucosa (pu / sis) two-component injectable hydrogel
WO2017206673A1